2018
DOI: 10.1080/00268976.2018.1483537
|View full text |Cite
|
Sign up to set email alerts
|

Neural-network-based order parameters for classification of binary hard-sphere crystal structures

Abstract: Identifying crystalline structures is a common challenge in many types of research. Here, we focus on binary mixtures of hard spheres of various size ratios, which stabilise a range of crystal structures with varying complexity. We train feed-forward neural networks to distinguish different crystalline and fluid environments on a single-particle basis, by analysing vectors composed of several averaged local bond order parameters. For all size ratios considered, we achieve a classification accuracy above 98% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Machine learning (ML) techniques are rapidly becoming a game-changer in the study of materials. Examples include speeding up computationally expensive calculations 5 , accurately distinguishing different crystal phases 6 , 7 , and even developing design rules for structural and material properties 8 . An exciting development is the design of UML algorithms that can autonomously classify particles based on patterns in their local environment 9 11 , even in disordered systems 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) techniques are rapidly becoming a game-changer in the study of materials. Examples include speeding up computationally expensive calculations 5 , accurately distinguishing different crystal phases 6 , 7 , and even developing design rules for structural and material properties 8 . An exciting development is the design of UML algorithms that can autonomously classify particles based on patterns in their local environment 9 11 , even in disordered systems 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In ref ( 60 ), a single-layer ANN, i . e ., only an input and output layer and no hidden layers, was employed to successfully classify the AB 13 phase from a binary fluid phase with a composition x L = 1/3 using the averaged bond order parameters as input.…”
Section: Resultsmentioning
confidence: 99%
“…14 Moreover, developments in the last few years have started to combine these local descriptions with supervised machine learning techniques in order to recognize specific crystal structures. [15][16][17][18] A very recent development has shown that this strategy can even be applied, with the aid of deep learning techniques, to simple coordinate information (instead of the standard local order descriptors). 19 In general, supervised learning strategies work very well to distinguish structures that we expect to form.…”
Section: Introductionmentioning
confidence: 99%